2020
DOI: 10.1177/0009922820906488
|View full text |Cite
|
Sign up to set email alerts
|

From Diagnosis to Treatment of Pediatric Tuberculosis: Ten Years Experience in a Single Institution

Abstract: Aim and Objectives. To describe the patient characteristics, clinical-epidemiologic-microbiologic profile, and treatment outcomes, and to draw attention to tuberculosis (TB) in Turkey. Methods. A retrospective, descriptive study was undertaken of 93 children aged 0 to 18 years who were admitted to Hacettepe University Pediatric Pulmonology Department for treatment from January 2005 to December 2015. Review of hospital records was performed for all children diagnosed as having TB. Results. Pulmonary TB was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…It is routinely applied to almost all children in the second month of life as a single dose 22 . The BCG vaccination rate in our center is similar to the rate in the general population of our country which is bigger than 90% 23,24 . All patients with NTM in this study already had BCG vaccination.…”
Section: Discussionsupporting
confidence: 81%
“…It is routinely applied to almost all children in the second month of life as a single dose 22 . The BCG vaccination rate in our center is similar to the rate in the general population of our country which is bigger than 90% 23,24 . All patients with NTM in this study already had BCG vaccination.…”
Section: Discussionsupporting
confidence: 81%
“…Çocuk yaş grubunda yeni tanı TB hastalığı çoğunlukla erişkin bir hasta kaynağını işaret etmekte olup sekiz hastamızda (%23.5) TB teması vardı; literatürde bu oran %29-46 arasında değişmektedir (10)(11)(12)(13). Temas öyküsü olguların hepsinde aile içi idi.…”
Section: Discussionunclassified
“…Also 29% of the patients had a history for contact with an adult index case. [1] In an another multicenter study from Turkey, 539 (50.8% male) children with TB aged 10 days-17 years (almost equal distribution in all age groups) from 16 different centers were evaluated over a 12 year period. The authors showed that contact with an index case was present in 39.8% of the patients and they concluded household contact screening techniques act very important role.…”
Section: Discussionmentioning
confidence: 99%
“…[5,6] Given the unclear non-specific syptoms, low bacillus load in respiratory samples and the low rate of microbiologic evidence, the rates of definitive diagnosis in childhood TB cases are very low. [1] In this study, we aimed to evaluate epidemiologic, clinical, laboratory, microbiologic features, treatment and outcomes of pediatric TB patients. We also aimed to describe the characteristics of immigrant patients due to the risk of uncontrolled migration to Turkey during this period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation